1,10-FENANTROLİNİN İMİDAZOL TÜREVLERİ İLE BAZI GEÇİŞ METAL KOMPLEKSLERİNİN SENTEZİ VE İNCELENMESİ - GÖMLEKSİZ, MESUT (Fırat Üniveristesi, 2007)
Bu çalısmada 2-(2-metoksifenil)-1H?imidazo[4,5-f][1,10]fenantrolin (L1), 2-p-tolil-1Himidazo[ 4,5-f][1,10]fenantrolin (L2), 4-bromo-2-(1H-imidazo[4,5-f][1,10]fenantrolin-2-il)fenol (L3), 2-(1H-imidazo[4,5-f][1,10]fenantrolin?2-il)?5?metoksifenol (L4) içeren organik ligandlar sentezlenmistir. Daha sonra farklı metal klorürleri kullanılarak kompleksleri elde edildi. Ligandların sentezi iki kademede gerçeklestirildi. Birinci kademede 1,10-fenantrolin, HNO3 + H2SO4 karısımı ve katalizör olarak NaBr reaksiyon kabına konarak sonuçda 1,10- fenantrolin-5,6-dion elde edildi. kinci kademede 1,10-fenantrolin-5,6-dion ile sırasıyla 2- metoksibenzaldehit, 4-metilbenzaldehit, 5-bromsalisilaldehit, 2-hidroksi?4-metoksibenzaldehit reaksiyona sokularak L1, L2, L3 ve L4 ligandları elde edildi. Üçüncü kademe olarak da bu ligandları kullanarak Cu(II), Ni(II), Co(II), Cd(II), kompleksleri elde edildi. Sentezlenen metal kompleksleri ve ligandların kimyasal yapıları, element analizi, IR, UV, 1H-NMR, TGA, molar iletkenlik, manyetik süseptibilite teknikleriyle tesbit edildi. Sentezlenen komplekslerin bozulmus oktahedral ve bozulmus kare piramit geometrik yapılarda oldukları tesbit edilmistir. Anahtar Kelimeler : 1,10-fenantrolin, 1,10-fenantrolin-5,6-dion, imidazol, kompleks.

In this study, organic ligands including 1,10-phenanthroline, 2-(2-methoxyphenyl)-1H? imidazo[4,5-f][1,10]phenanthroline (L1), 2-p-tolyl-1H-imidazo[4,5-f][1,10]phenanthroline (L2), 4-bromo-2-(1H-imidazo[4,5-f][1,10] phenanthroline-2-yl)phenol (L3), 2-(1H-imidazo[4,5- f][1,10] phenanthroline-2-yl )?5?methoxyphenol (L4) have been synthesized. Than their metal complexes were prepared by using chlorides of different metals. The synthesis of the ligands were carried out in two steps. At first step, 1,10- phenanthroline with HNO3+H2SO4 and NaBr as catalist were introduced to the reaction one by one and 1,10-phenanthroline-5,6-dione was obtanied. As a result at second step, the 1,10- phenanthroline-5,6-dione with 2-methoxybenzaldehyde, 4-methylbenzaldehyde, 5- bromosalyslaldehyde, 2-hydroxy-4-methoxybenzaldehyde were introduced to reaction one by one. The obtanied products are L1, L2, L3 and L4 ligands. At third step, by using these ligands, the Cu(II), Ni(II), Co(II), Cd(II) complexes were synthesized. The chemical structure of the synthesized metal complexes and ligands were determined by means of elemental analysis, IR, UV, 1H-NMR, TGA, molar conductivimetry and magnetic susceptibility techniques. It is observed that the synthesized complexes have distorted octahedral and distorted square pyramidal geometrical structures. Keywords: 1,10-phenanthroline, 1,10-phenanthroline-5,6-dione, imidazole, complexes
Synthesis and investigation of imidazole derivatives of 1,10-phenanthroline with some of their transition metal complexes
Keywords: Kimya